Presence of Salmonella spp. in One-day-old Chicks from Hatcheries in the Metropolitan Region of Fortaleza, Brazil - Átilla Holanda de Albuquerque (Acta Scientiae Veterinariae, 2014)
Background: Salmonellosis is caused by bacteria of the genus Salmonella and is a worldwide-considered major zoonosis with a risk for the public health due to the capacity of dissemination between animals and nature. In the poultry industry, day-old chicks may acquire the infection at the hatchery through contact with fomites and eggshells with the presence of contaminated feces, favoring the animal infection and may become a source of infection to other birds in the lot, as well as to several other animals, including man. The aim of this study was to verify the presence of Salmonella spp. in one-day-old chicks from hatcheries in the metropolitan region of Fortaleza, Brazil. Materials, Methods & Results: A transversal study with a convenience sampling was performed in 510 day-old chicks acquired from five hatcheries located in the metropolitan region of Fortaleza, Brazil. From each hatchery, 102 day-old chicks were analyzed at the Laboratory of Ornithological Studies (LABEO) of the State University of Ceará. Individual cloacal swab samples were collected immediately after arrival, following euthanasia by cervical dislocation for organ sampling, comprised of a pool of livers and yolk sacs of three birds per sample. Organ and cloacal samples were incubated in pre-enrichment using buffered peptone water 0.1%, following selective enrichment with the broths: Tetrathionate, Rappaport-Vassiliadis and Selenite-Cystine. After incubation, samples were streaked in Brilliant Green agar added Novobiocin (40 μg/mL) and MacConkey agar. For all the microbiological procedures, samples were incubated at 35 to 37°C for 18 to 24 h. Suspect colonies were identified by biochemical tests and confirmed with polyvalent O anti-Salmonella serum. Salmonella isolates were submitted to disk-diffusion method (Kirby-Bauer) following the National Committee for Clinical Laboratory Standards (NCCLS) guidelines. With the methodology applied, Salmonella spp. was not isolated from yolk sac or liver samples. From the five analyzed hatchery, two (40%) were positive for Salmonella Enteritidis. From the 510 samples analyzed, three were positive for Salmonella Enteritidis, resulting in a prevalence of 0.58% of all the cloacal swabs evaluated and the positive hatcheries presented prevalences of 1.96% and 0.98%. All three isolates were resistant to azithromycin and nalidixic acid in the susceptibility test. Discussion: The resistance of Salmonella to nalidixic acid in this study demonstrates the excessive use of this antibiotic as a prophylactic measure in breeder farms, therefore favoring the occurrence of resistant strains, which may be transmitted to other birds, animals and to man. The azithromycin resistant strains isolated in this study are important findings since this antibiotic is widely used in human treatment of infectious diseases that affect the genitourinary tract, respiratory system, oral cavity and skin. The results found in this study suggest further caution with the presenc